Intimate partner violence and unmet need for family planning in Afghan women: the implication for policy and practice - Omid Dadras; Takeo Nakayama; Masahiro Kihara; Masako Ono-Kihara; Fateme Dadras (BMC, 2022)
Plain language summary Intimate partner violence (IPV) involves not only physical, emotional, and sexual violence but also controlling behavior and could be associated with several adverse health outcomes. In this study, the authors used the data from Afghanistan Demographic and Health Survey (DHS) conducted in 2015 and explored the relationship between IPV and unmet need for family planning among Afghan women aged 18-49 years. IPV was observed in more than half of the Afghan women aged 18-49 years and almost 30% reported unmet needs for family planning. Interestingly, IPV was associated with a lower unmet need for family planning. This has been attributed to the reluctance of the victim woman to bring a child to the hostile environment and protect herself from acquiring the STDs that could be transmitted from a risky partner. Illiterate poor Afghan women were more likely to suffer from IPV and experience the unmet need for family planning. In addition, the rate of IPV was higher among Pashtun and Tajik ethnic groups; conversely, the rate of unmet need for family planning was low among them. The findings reflect on the most current situation of domestic violence among Afghan women and its impact on reproductive outcomes and the results could inform the international communities and human rights advocate to prevent the violence against Afghan women and improve their reproductive health.